2021
DOI: 10.3390/rs13193989
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Marine Heatwaves at the Sea Surface in the Northwestern Pacific Ocean in Summer 2021

Abstract: In July–August 2021, intense marine heatwaves (MHWs) occurred at the sea surface over extensive areas of the northwestern Pacific Ocean, including the entire Sea of Japan and part of the Sea of Okhotsk. In extent and intensity, these MHWs were the largest since 1982, when satellite measurements of global sea surface temperatures started. The MHWs in summer 2021 were observed at the sea surface and occurred concomitantly with a stable shallow oceanic surface boundary layer. The distribution of the MHWs was stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 41 publications
(42 reference statements)
2
29
0
Order By: Relevance
“…A mixed layer depth of 10 m was also related to the right peak of the frequency distribution of high SCCs as a function of mixed layer depth (Figure 7c). The period of the most extensive and intense marine heatwaves ("MHWs period") is based on Kuroda and Setou [14] and is indicated by a double-headed arrow.…”
Section: Relationships To Environmental Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…A mixed layer depth of 10 m was also related to the right peak of the frequency distribution of high SCCs as a function of mixed layer depth (Figure 7c). The period of the most extensive and intense marine heatwaves ("MHWs period") is based on Kuroda and Setou [14] and is indicated by a double-headed arrow.…”
Section: Relationships To Environmental Conditionsmentioning
confidence: 99%
“…In mid-September 2021, about a month after the subsidence of the most intense and extensive marine heatwaves over the north-western Pacific Ocean [14], an unprecedented large-scale outbreak of harmful algae occurred in Pacific coastal waters off the south-eastern coast of Hokkaido, Japan. There had been no previous reports of catastrophic disasters attributed to HABs over these coastal waters, although there were a few reports of occurrence of harmful algae in a limited area of this region during the 1970-1980s [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further analysis found that the reduction of cloud cover in the KOE was primarily explained by the anomalously strengthened North Pacific High (NPH) system (Figure 9a), which suppressed the convective activity, manifested as positive OLR and negative precipitation anomalies (Figure 9b,c). Similarly, Kuroda and Setou [19] found that MHW in the Northwest Pacific in summer 2021 was related to air-sea heat fluxes, and the northwestern shift of the NPH was an important factor. However, besides the NPH system, some other factors were still worthy of consideration.…”
Section: Impact Of Atmospheric Circulation Systemmentioning
confidence: 82%
“…Many MHWs, with diverse physical drivers, have been recorded over the global ocean [5,6]. The five major West Boundary Currents (WBCs) and their extension regions, the Oyashio region during summer in 2010-2016 were attributed to increased anticyclonic eddy activity; Kuroda and Setou [19] reported that a MHW occurred in July-August 2021 over the Northwest Pacific, including the entire Sea of Japan and part of the Sea of Okhotsk, which was mainly caused by anomalous surface heat flux forced by the atmospheric conditions.…”
Section: Introductionmentioning
confidence: 99%